System requirement analysis for e-learning materials to support academic writing skills for engineering students of vocational higher education - Dita Lupita Sari; Choirun Niswatin (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2018)
This paper outlines a system requirement of proposed e-learning design for English course particularly in academic writing. However, the system requirement is focused on functional requirement. Therefore, it is necessary to carry out an intensive interaction involving systems analysts and end-users to obtain the appropriate learning materials needed by the engineering students. The instrument of this research is interview and questionnaire. The former was elaborated by the English teachers, while the latter was collected from engineering students at Politeknik Kota Malang. The data collection is analyzed using Kano's method. The research findings indicates that the functional requirement consists of 3 parts: 1) academic writing, 2) quizzes, and 3) writing template. The academic writing is focused on how to write abstract. Meanwhile, the quizzes cover grammar, paraphrasing, and abstract organization. This application comes with an abstract template as well, which can be downloaded and printed as required affiliation.